Development of miniaturized control circuit of auto recloser earth leakage relay for a single phase 230V: article / Zulkifli Mat Yahya - Mat Yahya, Zulkifli (2013)
This paper presents development of miniaturized control circuit of auto recloser earth leakage relay for a single phase 230V in consumer unit as the protection devices. The study includes the development of control circuit of earth leakage relay (ELR) that response to the earth fault occurred due to lightning strike or short circuit. This control circuit will reconnect the circuit with utility supply automatically with a specific time that set without any human interface. The Peripheral Interface Controller (PIC) microcontrollers, PIC16F877A are used as the main component or element in the control circuit. The control circuits are used to control the contactor that act as a residual current device (RCD) to cut the power supply from the utility to assembly or electrical appliances when detected earth fault occurred by zero current transformer (ZCT) and sent the electrical signal to earth leakage relay (ELR). The protection devices are using ELR and contactor to replace the function of RDC, so the RCD does no longer use as protection devices. The simulation and development of control circuit are using PROTEUS simulation software.